2006
DOI: 10.1038/nri1775
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen–endoplasmic-reticulum interactions: in through the out door

Abstract: A key determinant for the survival of intracellular pathogens is their ability to subvert the cellular processes of the host to establish a compartment that allows replication. Although most microorganisms internalized by host cells are efficiently cleared following fusion with lysosomes, many pathogens have evolved mechanisms to escape this degradation. In this Review, we provide insight into the molecular processes that are targeted by pathogens that interact with the endoplasmic reticulum and thereby subver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 130 publications
0
79
0
5
Order By: Relevance
“…A satisfying aspect of this explanation of viral suppression is that it readily explains the ability of Wolbachia to suppress RNA viruses, and not DNA viruses, which preferentially replicate in the nucleus (den Boon et al 2010). A number of other intracellular bacteria also exhibit a close association with the ER (Roy et al 2006). It will be of great interest to determine whether these also suppress positive-strand RNA viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…A satisfying aspect of this explanation of viral suppression is that it readily explains the ability of Wolbachia to suppress RNA viruses, and not DNA viruses, which preferentially replicate in the nucleus (den Boon et al 2010). A number of other intracellular bacteria also exhibit a close association with the ER (Roy et al 2006). It will be of great interest to determine whether these also suppress positive-strand RNA viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic cell uptake, mediated by a range of opsonic and non-opsonic receptors, induces an antiinflammatory response, consistent with the need for safe clearance [59]. There is considerable controversy regarding the role of TLR in regulating the kinetics of phagosome maturation [60], and also in the extent to which the endoplasmic reticulum might contribute [61] to formation of phagosomes; some intracellular pathogens are able to direct the composition of the phagosome membrane, to locate in immature phagosomes, and to recruit Golgi/ER membranes [62] and/or disrupt the phagosome membrane in order to enter the cytosol. In particular Listeria monocytogenes has proved a dramatic and effective agent to alter the intracellular dynamics of actin assembly after infection [63,64].…”
Section: Microbial Recognition and Macrophage Responsesmentioning
confidence: 99%
“…Thus, the triggering of apoptosis could actually be part of the innate host defense system to prevent chronic infection by these organisms. In this regard, there is evidence that intracellular organisms activate the UPR as a mechanism to support synthesis of pathogen proteins (41)(42)(43), and these organisms also display PAMPs that can activate scavenger receptors and TLRs. Most interestingly, in vitro studies have shown that macrophage apoptosis is associated with control of infection by M. tuberculosis (40), and genetic studies in mice have shown an association between resistance to infection by M. tuberculosis and induction of macrophage apoptosis (44).…”
Section: The Roles Of Er Stress and Pattern Recognition Receptors In mentioning
confidence: 99%
“…However, there are classes of infectious organisms that depend upon living macrophages to survive. Examples include viruses and intracellular bacteria, such as Mycobacterium tuberculosis and Brucella species (40,41). Thus, the triggering of apoptosis could actually be part of the innate host defense system to prevent chronic infection by these organisms.…”
Section: The Roles Of Er Stress and Pattern Recognition Receptors In mentioning
confidence: 99%